A methodology to quantify the gas supply capacity of natural gas transmission pipeline system using reliability theory. (July 2018) - Yu, Weichao; Wen, Kai; Min, Yuan; He, Lei; Huang, Weihe; Gong, Jing
Highlights: A methodology is developed to quantify the gas supply capacity of pipeline system. Two reliability indicators are proposed to assess the gas supply capacity. Two case studies are adopted to confirm the feasibility of the methodology. The impact of the line pack on the gas supply capacity is investigated. Abstract: A methodology to quantify the gas supply capacity of a natural gas transmission pipeline system is developed in this paper. The methodology is based on reliability theory and hydraulic analysis of unsteady flow. Considering the state transition process and change law of the flow rate, two reliability indicators, gas supply satisfaction ( Sa ) and gas supply supportability ( Su ), are proposed to quantify the gas supply capacity. The methodology is first able to simulate the state transition process and the duration of each operating state based on Monte Carlo approach, and then the hydraulic analysis of unsteady flow after the system transits to others states is applied to analyze the change law of the actual flow rate through the commercial software SPS (Stoner Pipeline Simulator). By combining the hydraulic analysis into the simulation of state transition process, the two reliability indicators are calculated. A detailed procedure for gas supply capacity evaluation of a natural gas transmission pipeline system is presented, and its feasibility is confirmed with two case studies including a hypothesis and a real transmission pipeline system. Furthermore, impacts of the line pack, availability of the components and the number of stand-by units on the gas supply capacity are investigated.